Edukasi Gizi “Healthy Food and Life Style to Increase Working Memory Capacity” Siswi MTs (Madrasah Tsanawiyah) Al-Fatah - Afiska Prima Dewi; Ritma Dewanti; Hernianti Hernianti; Syamsopyan Syamsopyan; Suherman Suherman (Jurnal Pengabdian Bidang Kesehatan, 2025)
Working memory capacity is a crucial aspect of cognitive function that plays a significant role in supporting students' learning processes. Working memory functions as a temporary storage system that allows individuals to store and manipulate information quickly. In an educational context, optimal working memory capacity can improve students' ability to understand, process, and remember information presented during the teaching and learning process. Several factors known to influence working memory capacity include breakfast habits, nutritional status, body fat percentage, and hemoglobin (Hb) levels. These factors are closely related to students' daily nutritional intake and healthy lifestyle. This Community Service (PkM) activity, with the topic "Healthy Food and Lifestyle to Increase Working Memory Capacity," aimed to increase students' understanding and awareness of the importance of a healthy diet and an active lifestyle in supporting cognitive function, particularly working memory. This activity was held in July 2024 at MTs (Madrasah Tsanawiyah) Al Fatah, Natar District, Lampung Regency. The implementation method was interactive nutrition education, covering the importance of a nutritious breakfast, consuming a balanced diet, physical activity, and general health care. Based on the results of evaluations conducted before and after the activity, there was an increase in the average knowledge scores of female students, as well as a significant difference in their understanding of the concepts of healthy eating and a lifestyle that supports working memory function. These findings indicate that nutrition education interventions have significant potential to improve the quality of learning by enhancing students' cognitive aspects. This activity is expected to become a model that can be implemented sustainably in other school settings.